Health Policy Perspectives on Combating Diarrhea in Toddlers - Muhammad Alwy Arifin; Dian Saputra Marzuki (Yayasan Sinergi Kawula Muda, 2025)
Diarrhea remains a significant cause of morbidity and mortality among children under five, particularly in low- and middle-income countries. Health policies targeting the prevention and management of diarrhea in toddlers have evolved over the years, yet challenges persist. This literature review examines the effectiveness of existing health policy interventions, identifies gaps, and suggests potential avenues for improving outcomes in combating diarrhea in toddlers. The review underscores the need for integrated and context-specific approaches that address the multifaceted determinants of diarrheal diseases.